Non-Invasive Ventilation with Neurally Adjusted Ventilatory Assist (NAVA) Improves Extubation Outcomes in Extremely Low-Birth-Weight Infants - Kevin Louie; Shaili Amatya; Gad Alpan; Lance A. Parton (MDPI AG, 2024)
Objective: This study investigates the effectiveness of extubation from conventional mechanical ventilation using an endotracheal tube (MVET) compared to synchronized non-invasive positive-pressure ventilation (sNIPPV) using neurally adjusted ventilatory assist (NAVA) and conventional non-invasive positive-pressure ventilation (NIPPV) in extremely low-birth-weight (ELBW) infants. Methods: An institutional review board (IRB) approved this study (#12175) to conduct a single-center randomized control trial including 60 ELBW infants assigned in a one-to-one computer-generated scheme to either sNIPPV using NAVA or NIPPV. The primary outcome involved the need for reintubation, and the secondary outcome involved the assessment of moderate/severe BPD, defined as an oxygen requirement at 36 weeks, as in #NCT03613987 (clinicaltrials.gov). Results: There were 60 ELBW infants enrolled and randomized. The overall gestational age was 26 (1.5) weeks, and the birth weight was 773 (157) g [mean (SD)]. There were no statistically significant differences between the NAVA and NIPPV patient characteristics. There was a 41% extubation failure rate in the NIPPV group and 35% in the NAVA group (p = NS). The NAVA group had less moderate and severe BPD (p = 0.03), a shorter oxygen therapy duration (p = 0.002), a decreased length of stay (p = 0.03), and less need for home oxygen (0, 43%; p = 0.0004). Conclusions: This study found similar extubation failure rates among ELBW infants as in prior studies. However, the NAVA group had lower rates of moderate/severe BPD and need for oxygen at discharge, as well as shorter oxygen therapy duration and length of stay. The use of NAVA may be a reasonable alternative mode of non-invasive ventilation in the ELBW population.